Prevalence of anxiety among the adult population during the COVID-19 pandemic in Uttar Pradesh - Dixit, Priyanshi; Thakur, Shafali; Chauhan, Soni; Tiwari, Surya Kant; Srivastava, Saumya P. (International Journal Of Community Medicine And Public Health, 2022)
Background: The COVID-19 pandemic had a negative impact on the mental health of the global population. The purpose of this study is to investigate anxiety levels of adult population in relation to the COVID-19 pandemic. Methods: The study utilized a web-based cross-sectional survey design. A total of 236 participants were enrolled via snowball sampling method. Standardized tool coronavirus anxiety scale was used to collect the data regarding COVID-19 related anxiety. The data was collected during August-November 2021. Results: Statistical analysis was done using SPSS version 20. The mean age of the participants was 26.64+8.38 years, with the majority being female (65.3%). Approximately half (48.3%) of the participants were healthcare professionals (HCWs). The results revealed that only 5.5% of the participants were anxious about COVID-19, with healthcare workers being the most anxious. Conclusions: During the COVID-19 crisis, appropriate supportive interventions should be implemented with the goal of providing targeted mental health services to those who are more likely to suffer from mental disorders. The psychosocial intervention and support strategy should cover specifically frontline workers who are tasked with the role of combating virus.